Deletion of the mitochondrial calcium uniporter in adipose tissue promotes energy expenditure and alleviates diet-induced obesity - Mengting Jia; Siqi Liu; Yang Xiao; Zhiwang Zhang; Mingming Li; Xinyu Qi; Xinyi Qi; Lin Yu; Caiyong Zhang; Tianyu Jiang; Tingli Pan; Yu Sun; et al. (Elsevier, 2024)
Objective: Studies have shown a correlation between obesity and mitochondrial calcium homeostasis, yet it is unclear whether and how Mcu regulates adipocyte lipid deposition. This study aims to provide new potential target for the treatment of obesity and related metabolic diseases, and to explore the function of Mcu in adipose tissue. Methods: We firstly investigated the role of mitoxantrone, an Mcu inhibitor, in the regulation of glucose and lipid metabolism in mouse adipocytes (3T3-L1 cells). Secondly, C57BL/6J mice were used as a research model to investigate the effects of Mcu inhibitors on fat accumulation and glucose metabolism in mice on a high-fat diet (HFD), and by using CRISPR/Cas9 technology, adipose tissue-specific Mcu knockdown mice (Mcufl/+ AKO) and Mcu knockout of mice (Mcufl/fl AKO) were obtained, to further investigate the direct effects of Mcu on fat deposition, glucose tolerance and insulin sensitivity in mice on a high-fat diet. Results: We found the Mcu inhibitor reduced adipocytes lipid accumulation and adipose tissues mass in mice fed an HFD. Both Mcufl/+ AKO mice and Mcufl/fl AKO mice were resistant to HFD-induced obesity, compared to control mice. Mice with Mcufl/fl AKO showed improved glucose tolerance and insulin sensitivity as well as reduced hepatic lipid accumulation. Mechanistically, inhibition of Mcu promoted mitochondrial biogenesis and adipocyte browning, increase energy expenditure and alleviates diet-induced obesity. Conclusions: Our study demonstrates a link between adipocyte lipid accumulation and mCa2+ levels, suggesting that adipose-specific Mcu deficiency alleviates HFD-induced obesity and ameliorates metabolic disorders such as insulin resistance and hepatic steatosis. These effects may be achieved by increasing mitochondrial biosynthesis, promoting white fat browning and enhancing energy metabolism.